Antixenosis and antibiosis characterization on soybean cultivars of Anticarsiagemmatalis (Lepidoptera: Erebidae) - Fabrício de Lima; Otacílio Divino Rezende Neto; Frederico Landim Teixeira; Márcio da Silva Araújo; André Cirilo de Sousa Almeida; Edson Hirose; Flávio Gonçalves de Jesus (Ciência Rural, 2023)
ABSTRACT: Anticarsia gemmatalis (Lepidoptera: Erebidae) is distributed in tropical and subtropical regions of America, and is an important pest of Fabaceae, such as: soybean, peanut, common bean, cowpea, pea, chickpea and kudzu. In soybean, the velvet bean caterpillar is important due to the plant defoliation in their larval stage. This study evaluated soybean cultivars as source of resistance to A. gemmatalis by antixenosis (attractiveness and non-preference for feeding) and antibiosis (biological parameters of the insect). The parameters evaluated were: antixenosis: attractiveness and non-preference, dry mass consumed and attractiveness index and antibiosis: duration of larval and pupal stages, adult longevity, total cycle, larval and pupal weights and larval, pupal and total viability. Considering antixenosis and antibiosis the least suitable cultivars for A. gemmatalis were found to be BRS 8383 IPRO, BRS 1074 IPRO, BRS 1061 IPRO, BRS 7180 IPRO, BRS 9383 IPRO, BRS 8980 IPRO and BRS 1003 IPRO due to high mortality in the larval phase. The cultivars BRS 523 and BRS 543 RR “block technology” suggest displays antixenosis and or antibiosis to A. gemmatalis. These cultivars can be used by soybean producers in combination with other control tactics in soybean IPM.